Nitrogen management schedule for Bt cotton under different planting geometries in semi-arid north-western plains of India - Kaur, Ramanjit; Dass, Anchal; Verma, V.P (Annals of Agricultural Research, 2016)
Cotton occupies a predominant position amongst all cash crops in India. However, the full proofagronomic practices are still lacking, particularly for Bt. cotton. Therefore, a field experiment wasconducted at research farm of ICAR-IARI, New Delhi during kharif seasons of 2013 and 2014 todetermine precise nitrogen (N) application rate and planting geometries for Bt. Cotton. The treatmentsconsisted of four planting geometries viz., 75 × 60 cm (R), 75 × 45 cm, 60 × 45 cm and 90 × 60 cm andfive N-application methods viz., recommended dose of N (RDN), site specific nutrient managementusing SPAD meter (SPAD index